Making Administrative Work Visible : Data-Driven Advocacy for Understanding the Labor of Writing Program Administration - Szymanski, Natalie; Napolitano, Frank M.; Miller-Cochran, Susan K.; Hudgins, Remi; Halasek, Kay; Graziano, Leigh (Book collections on Project MUSE., 2023)
"Making Administrative Work Visible brings together graduate students, associated faculty, administrative staff, and tenured and tenure-track faculty at community colleges, regional state universities, liberal arts colleges, private colleges, and research-intensive institutions across the country to speak to the challenges faced by those who do writing program administration work"--